2017
DOI: 10.1039/c7ra11270j
|View full text |Cite
|
Sign up to set email alerts
|

Brachyantheraoside A8, a new natural nor-oleanane triterpenoid as a kidney-type glutaminase inhibitor fromStauntonia brachyanthera

Abstract: With the aim of finding a better kidney-type glutaminase (KGA) inhibitor with potential anti-cancer properties, 18 nor-oleanane triterpenoids fromStauntonia brachyanthera, including 2 new ones, were screened against KGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Human hepatoma HepG2 and lung carcinoma A549 cells are found to show high expression levels of GAB and KGA protein . KGA was also found to be highly expressed in SW1990 and erlotinib-resistant NSCLC cells HCC827-ER . Finally, the methods for counting live cells mainly include CellTiter Glo Luminescent Cell Viability Assay kit (Promega) and trypan blue dye exclusion in a hemocytometer.…”
Section: Assays To Monitor Gls1modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human hepatoma HepG2 and lung carcinoma A549 cells are found to show high expression levels of GAB and KGA protein . KGA was also found to be highly expressed in SW1990 and erlotinib-resistant NSCLC cells HCC827-ER . Finally, the methods for counting live cells mainly include CellTiter Glo Luminescent Cell Viability Assay kit (Promega) and trypan blue dye exclusion in a hemocytometer.…”
Section: Assays To Monitor Gls1modulationmentioning
confidence: 99%
“…Physapubescin and Brachyantheraoside A 8 (Figure ), two novel kidney-type glutaminase (KGA) inhibitors, were identified from natural products by structure-based virtual screening. , The enzyme inhibition experiments indicated that the IC 50 values of physapubescin and brachyantheraoside A 8 were 9.89 and 6.10 μM, respectively, with a closely similar effect compared with BPTES (IC 50 = 8.60 μM). The cell-based assays revealed that the IC 50 value of physapubescin against HCC827-ER and HT1080 cells were 2.73 and 6.99 μM, respectively, and the IC 50 value against the HCC1806 cell was 24.94 μM.…”
Section: Modulators Of Glsmentioning
confidence: 99%
“…caused the enzyme to reduce aggregation), C9 did not exhibit such an effect. Natural-product inhibitors have also been identified, including physapubescin [ 73 ] and brachyantheraoside A8 [ 79 ]. Interestingly, physapubescin shares structural similarity with the benzophenathridinone class of inhibitors, displaying even lower IC 50 .…”
Section: Molecular Basis For Glutaminase Inhibitionmentioning
confidence: 99%
“…Resveratrol, in combination with cisplatin, shows synergistic effects on decreasing glutamine uptake by downregulating ASCT2 in human hepatoma cells . After glutamine enters the cells, it is first converted to glutamate by glutaminase (GLS), thus glutaminase is considered to be a “gate-keeper” enzyme of glutaminolysis. , The GLS1 isozyme (kidney-type glutaminase) is a downstream target of Myc and a highly upregulated isoform of GLS in many cancers with poor prognosis. ,, Brachyantheraoside A8 blocks glutamine metabolism by inhibiting the enzymatic activity of GLS1 in breast cancer . Physapubescin k allosterically inhibits GLS1 activity in non-small cell lung cancer (NSCLC) and human fibrosarcoma cells .…”
Section: Phytocompounds Inhibiting Metabolism Of Cancermentioning
confidence: 99%